Human Resource Information Systems and Organizational Performance: The Mediating Role of Digital Competence in Private Higher Education Institutions in Makassar - Andi Irsandi Yusri; Amar Sani; Muhammad Difky Al Qadri; Reza Fadel Muhammad; Firisqi Nuryanti (Yayasan Vifada Cendikia Indonesia, 2026)
Digital transformation has encouraged higher education institutions to optimize the implementation of Human Resource Information Systems (HRIS) to improve human resource management and organizational performance. However, the effectiveness of HRIS implementation depends not only on system quality but also on users' digital competence in utilizing technology effectively. This study aims to examine the effect of Human Resource Information System (HRIS) on organizational performance through digital competence in private higher education institutions in Makassar, Indonesia. This study employed a quantitative approach using a survey method involving 200 lecturers and administrative staff selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that Human Resource Information System (HRIS) has a positive and significant effect on digital competence. Digital competence also has a positive and significant effect on organizational performance. Furthermore, HRIS directly influences organizational performance. The mediation analysis indicates that digital competence partially mediates the relationship between HRIS and organizational performance. These findings suggest that organizational performance improvement is determined not only by the implementation of information technology but also by the capability of human resources to utilize digital technology effectively. This study contributes to the development of digital human resource management literature and provides practical implications for private higher education institutions in optimizing HRIS implementation through the enhancement of digital competence